KNOWLEDGE ABOUT HEPATITIS B INFECTION AMONG MEDICAL STUDENTS IN ERBIL CITY, IRAQ - Othman, Samir M; Saleh, Abubakir M; Shabila, Nazar P (European Scientific Journal, ESJ, 2014)
Background: Health care personnel especially medical student represent high risk population for hepatitis B virus infection. Objective: This study sought to assess the knowledge of medical students regarding hepatitis B infection and its transmission and prevention. Methods: A cross-sectional study was conducted on 200 medical students in Erbil, the main city of Iraqi Kurdistan region. A self-administered questionnaire was used for data collection. In addition to basic demographic characteristics, the questionnaire included 18 questions about routes and modes of transmission, sequel and prevention of HBV. The students were also asked about their vaccination status. Statistical package for social sciences was used for data analysis. Results: A high proportion of the study participants (41%) had poor knowledge about HBV while 45% had acceptable knowledge and 14% had good knowledge. Good knowledge score was significantly higher among older students and students in clinical year study, p <0.001. Only 45% of them were vaccinated against HBV. The vaccination rate was higher among clinical year study students (68%) in comparison to pre-clinical year students (22%), p <0.001. The vaccination rate was highest among those who had good knowledge (100%), in comparison to those with acceptable knowledge (53.3%) and poor knowledge (17.1%), p <0.001. Conclusions: Knowledge about HBV among the medical students in Hawler Medical University is relatively poor, with important gaps which need to be strengthened. A critical level of public awareness and vaccination coverage, particularly among young students, are essential to decrease burden of the disease in Erbil in the future.